Studi Komparatif Kinerja Guru Senior dan Guru Junior dalam Pengelolaan Pembelajaran pada SMP Negeri Kecamatan Padang Utara - Helen Listalia; Lusi Susanti; Anisah, Anisah; Singgih Ginanjar (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to investigate the performance differences between senior teachers (teaching experience >10 years) and junior teachers (<10 years) in managing learning at public junior high schools in Padang Utara District. A quantitative approach with a descriptive comparative design was used. The sample consisted of 102 teachers selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire measuring four indicators: quality, quantity, timeliness, and responsibility. Data analysis used the Mann-Whitney U non-parametric test. The results showed that the performance of both groups was in the "Good" category, with the Respondent Achievement Rate of senior teachers at 86.25% and junior teachers at 80.64%. The hypothesis test (Sig. 0.001 < 0.05) proved a significant difference. Senior teachers are superior in quality stability and timeliness, while junior teachers excel in learning interactions but face challenges in time management.